Creative thinking ability for each self-efficacy level on challenge-based on ethnomathematics learning class with AR-comic book - Ardiansyah, Adi Satrio; Wulandari, Annisa; Setiawan, Ananda Verry; Mulyono (Journal on Mathematics Education, 2026)
The development of creative thinking has emerged as a central objective in contemporary mathematics education, reflecting the need to cultivate higher-order cognitive competencies essential for twenty-first-century learning. While ethnomathematics provides culturally situated contexts that enhance the relevance and meaning of mathematical concepts, augmented reality (AR) offers advanced visualization and engagement opportunities that enrich learning experiences. Nevertheless, empirical investigations that integrate challenge-based learning, ethnomathematics, and AR-assisted media remain scarce. Moreover, limited attention has been given to understanding how students’ self-efficacy influences creative thinking within such an integrative pedagogical framework. This study seeks to evaluate the pedagogical quality of a challenge-based ethnomathematics model supported by an Augmented Reality Comic Book in fostering students’ creative thinking abilities. Specifically, it examines the effect of self-efficacy on creative thinking performance within this model and characterizes students’ creative thinking profiles across different self-efficacy levels. A mixed-methods design employing a concurrent embedded strategy was implemented. Data were collected through creative thinking assessments, self-efficacy questionnaires, classroom observations, and semi-structured interviews. Quantitative data were analyzed using inferential statistical techniques, while qualitative data underwent systematic analysis through data reduction, display, conclusion drawing, and triangulation procedures. The findings indicate that the proposed instructional model satisfies established quality criteria. Students’ self-efficacy accounts for 52.1% of the variance in creative thinking, with higher self-efficacy levels associated with stronger manifestations of fluency, flexibility, and originality. These results provide empirical evidence for the efficacy of culturally grounded, technology-enhanced challenge-based learning in strengthening students’ creative mathematical competencies and advancing contemporary pedagogical practice.